2021
DOI: 10.1007/s40279-021-01582-y
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Exercise and Sports: A Systematic Review

Abstract: Metabolomics can improve the understanding of the physiological responses to exercise training and determinants of sport performance.• While untargeted metabolomics studies with small sample sizes, invasive sampling methods and a focus on short term effects of exercise have dominated exercise metabolomics studies, there is currently a trend towards longer term, biomarker-based studies with larger numbers of subjects using noninvasive sampling.• Improvements in study design, method standardization and data inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 163 publications
0
52
0
Order By: Relevance
“…Urine provides an alternative noninvasive matrix for the discovery of biomarkers 5 , 46 . "Albumin in urine is a critical marker in the assessment of kidney damage, but the diagnosis can be even more precise if the values of CysC and serum creatinine level are also associated with it" 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine provides an alternative noninvasive matrix for the discovery of biomarkers 5 , 46 . "Albumin in urine is a critical marker in the assessment of kidney damage, but the diagnosis can be even more precise if the values of CysC and serum creatinine level are also associated with it" 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Sportomics is a subject-centered holistic method that focuses on sports as the metabolic challenge 1 (for an editorial and reviews, see Bragazzi 2020; Bassini and Cameron 2014; Sellami et al 2022) 2 4 . In addition, the use of metabolomics is rapidly gaining space in understanding exercise and sports 5 . We have been utilizing sportomics and other in-field exercise models to understand hypermetabolic stress in health and disease 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the results presented, there are numerous other articles found in the literature that deal with metabolic changes in exercise [ 145 , 146 , 147 ] which shows the great potential of the method in the study of health and diseases and the impact of exercise intervention on metabolic pathways. However, the effects on the processes of cell proliferation, changes in gene activity can only be inadequately mapped.…”
Section: Metabolomicsmentioning
confidence: 96%
“…Recently, scholars have also assessed the epigenetics changes in athletes, establishing a new super-specialty termed as “sports epigenetics/epigenomics” ( Zimmer et al, 2016 ). Other biomarkers have been identified at the level of the metabolome ( Khoramipour et al, 2021 ), immunome ( Nieman and Pence, 2020 ) and microbiome ( Mohr et al, 2020 ), among others.…”
Section: Sports Sciences Exercise and Physical Activitymentioning
confidence: 99%
“…Finally, Khoramipour and others ( Khoramipour et al, 2021 ) were able to identify five major categories covered by sports and exercise metabolomics/metabonomics studies: namely, i) exercise metabolism; ii) exercise metabolism with focus on nutritional aspects; iii) sports metabolism; iv) exercise metabolism with an emphasis on clinical implications; and v) metabolome assessments and comparisons. Authors found that exercise metabolism was the research area most addressed by scholarly investigations, generally utilizing blood and urine samples but relying on untargeted, qualitative rather than targeted, quantitative platforms.…”
Section: Sports Proteomics and Metabolomics/metabonomicsmentioning
confidence: 99%